Distributed Evaluation Systems for Large Language Models: A Technical Overview - Gaurav Bansal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively examines distributed evaluation systems for large language models (LLMs) in enterprise environments. As organizations increasingly deploy LLMs in mission-critical applications, the need for robust, scalable evaluation frameworks has become paramount. The article explores the architectural foundations of these systems, including hub-and-spoke designs with specialized evaluation nodes that work in concert to assess multiple quality dimensions simultaneously. It analyzes the evolution of evaluation methodologies beyond traditional accuracy metrics to include multidimensional assessment frameworks that evaluate factual correctness, reasoning coherence, instruction following, and output safety. Implementing automated testing pipelines, human judgment correlation, and continuous performance monitoring creates holistic evaluation ecosystems essential for responsible AI deployment. Through a detailed examination of practical applications in customer service, content generation, and decision support systems, the article highlights how distributed evaluation frameworks enable organizations to maintain reliability while accelerating improvement cycles. The article concludes by addressing persistent challenges in evaluation and outlining future directions, including simulation-based testing, integration with development workflows, and evolving regulatory requirements for AI governance.